Islamism and Politics - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah: Journal of Islamic Studies, 2010)
Indonesia has witnessed the growing role of Majelis Ulama Indonesia (MUI, Indonesian Ulama Council) and excessive introduction of shari‘a in Aceh in the last decade. Undoubtedly, the MUI has played important role in defining Islam, or, to be precise, Islamic orthodoxy in the country especially after the downfall of Soeharto regime. Considering itself as the inheritor of the prophet, MUI claims to hold the sole religious authority for guiding Muslim umma in the country in all aspects of life, including people’s beliefs. In this current volume of Al-Jamiah, an articles deals with the MUI discussing its controversial fatwa on Ahmadiyah that is charged of spreading deviated beliefs. Ismatu Ropi in his writing analyses the fatwa of Majelis Ulama Indonesia (MUI) on Ahmadiyah and its impacts on more stained relationship within Muslim community in Indonesia. He examines socio-political natures before and after the fatwa on Ahmadiyah reissued in 2005 (the first fatwa was issued in the 1980s) in the lights of the emergence of new model of Islamism in Indonesia and the more conservative shift within the MUI itself particularly after the collapse of Soeharto regime.